Electrolyte, secondary battery, and device
By using a combination of fluorine-containing lithium sulfonimide and fluorine-containing sulfonic acid additives in the electrolyte, the content ratio is controlled, and the problem of fluorine-containing lithium sulfonimide corrosion of aluminum foil at high voltage is solved, which significantly improves the battery Cycling and multiplying performance and improve battery safety performance.
Patent Information
- Application Number
- CN202311030490.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
Lithium fluorosulfonimide is prone to corrode aluminum foil at high voltages, limiting its application in high voltage battery systems, and existing solutions require the addition of a large number of other lithium salts, resulting in increased battery impedance and severe gas production.
The electrolyte that combines lithium fluorosulfonimide and fluorosulfonic acid additives is used to suppress corrosion of aluminum foil by controlling the content ratio of the two (1≤H/S≤35) and improve the cycle performance and rate performance of the battery.
It significantly improves the cycling performance and rate performance of the secondary battery under high voltage, improves the stability and thermal stability of the electrolyte, and enhances the safety performance of the battery.
Smart Images

Figure BDA0004397770130000041 
Figure BDA0004397770130000051 
Figure BDA0004397770130000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to an electrolyte, a secondary battery and a device. Background Art
[0002] At present, lithium hexafluorophosphate (LiPF 6 ) is a commonly used lithium salt in lithium-ion batteries due to its comprehensive advantages such as high ionic conductivity, wide electrochemical window, and good film-forming properties on the surface of positive and negative electrodes. 6 It is easy to decompose at high temperature and is extremely sensitive to moisture, producing highly toxic PF 5 In addition, for high-voltage and high-capacity cathode systems such as high-nickel ternary and lithium-rich manganese-based, the presence of HF in the electrolyte will cause the transition metal to dissolve, thereby destroying the structural integrity of the cathode material, accelerating the attenuation of battery capacity and the deterioration of cycle stability. Therefore, LiPF 6 It is difficult to apply to special battery systems with high energy density.
[0003] In recent years, as a new type of lithium salt, fluorinated lithium sulfonyl imide is expected to become LiPF 6 One of the alternatives that has been widely studied is the lithium salt and LiPF 6 The price is similar, and it is more soluble in carbonate solvents than LiPF 6 It has higher ionic conductivity, and its thermal stability and water stability are better than LiPF 6 . In addition, the interface protection film formed by the lithium salt on the surface of the positive electrode and the surface of the negative electrode has lower impedance, which is beneficial to the improvement of battery rate performance. However, the lithium salt is easy to corrode the aluminum foil as the positive electrode current collector under high voltage, and this disadvantage limits its application in high-voltage battery systems. In response to this problem, some reports in literature and patents show that the use of boron-based lithium salts such as lithium bis(oxalatoborate) (LiBOB) or lithium difluorooxalatoborate (LiDFOB), as well as LiPF 6 Although the problem of lithium fluoride sulfonyl imide corroding aluminum foil under high voltage can be improved to a certain extent by mixing lithium salts such as LiPF with fluorine sulfonyl imide, a large amount of these lithium salts (20% to 40%) need to be added, which will bring other problems. 6 If too much is added, the electrolyte will inherit LiPF 6 disadvantages; when the amount of boron lithium salts such as LiBOB or LiDFOB is added in large quantities, the battery impedance becomes larger and the gas production is serious.
[0004] Therefore, it is of great significance to develop high-performance aluminum foil corrosion-resistant additives to prevent the corrosion of aluminum foil by fluorinated sulfonyl imide lithium, thereby realizing the application of fluorinated sulfonyl imide lithium in high-voltage battery systems and improving the battery safety performance to a certain extent. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present application provides an electrolyte, a secondary battery and a device.
[0006] The first aspect of the present application provides an electrolyte, which includes: a fluorinated lithium sulfonyl imide and a fluorinated sulfonic acid additive, wherein the fluorinated sulfonic acid additive includes RL-SO 3 M; wherein L is selected from fluorinated C 1 -C 6 Alkylene or fluorinated C 1 -C 6 Alkenylene, R is selected from fluorine, fluorinated C 1 -C 6 Alkyl, fluorinated C 1 -C 6 Alkenyl, fluorinated C 6 -C 12 An aryl group or a fluorosilyl group, M is selected from lithium or sodium; based on the mass of the electrolyte, the mass percentage of the fluorinated sulfonyl imide lithium is H%, and the mass percentage of the fluorinated sulfonic acid additive is S%, satisfying: 1≤H / S≤35.
[0007] A second aspect of the present application provides a secondary battery, which includes the aforementioned electrolyte.
[0008] A third aspect of the present application provides a device, which includes the aforementioned secondary battery.
[0009] The technical solution of this application can achieve the following beneficial effects:
[0010] The electrolyte of the present application uses lithium fluorinated sulfonyl imide as a lithium salt, and uses a fluorinated sulfonic acid additive as an anti-corrosion additive. By controlling the ratio of the content of lithium fluorinated sulfonyl imide and the fluorinated sulfonic acid additive, the problem of lithium fluorinated sulfonyl imide corroding the aluminum foil as a positive electrode current collector under high pressure is solved, and the cycle performance and rate performance of the secondary battery under high pressure are significantly improved; in addition, the organic part of the fluorinated sulfonic acid additive has a large steric hindrance and is substituted by fluorine atoms, so that the polarity and surface energy of the fluorinated sulfonic acid additive are reduced, thereby ensuring that the fluorinated sulfonic acid additive is not easy to dissolve or swell in the electrolyte, and further, it is also beneficial to maintain the stability of the electrolyte; further, the electrolyte has excellent thermal stability, and the high temperature performance and safety performance of the secondary battery are also greatly improved. DETAILED DESCRIPTION
[0011] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0012] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0013] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0014] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0015] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0016] The term "C 1 -C 6 The "alkyl" group may be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl or n-hexyl, etc.
[0017] The term "C2-C6 alkenyl" may be ethenyl, propenyl, butenyl, pentenyl or hexenyl.
[0018] The term "C1-C6 alkylene" may be methylene, ethylene, n-propylene, isopropylene, n-butylene, isobutylene, tert-butylene, n-pentylene, isopentylene or n-hexylene, or the like.
[0019] The term "C2-C6 alkenylene" may be ethenylene, propenylene, butenylene, pentenylene or hexenylene.
[0020] The term "C6-C12 aryl" may be phenyl or naphthyl, and the like.
[0021] The term "silyl" may refer to silicon-substituted analogs of carbon alkanes.
[0022] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0023] 1. Electrolyte
[0024] One or more embodiments of the present application provide an electrolyte, including: a fluorinated lithium sulfonyl imide and a fluorinated sulfonic acid additive, wherein the fluorinated sulfonic acid additive includes RL-SO 3 M; wherein L is selected from fluorinated C 1 -C 6 Alkylene or fluorinated C 1 -C 6 Alkenylene, R is selected from fluorine, fluorinated C 1 -C 6 Alkyl, fluorinated C 1 -C 6 Alkenyl, fluorinated C 6 -C 12 Aryl or fluorosilyl, M is selected from lithium or sodium; based on the mass of the electrolyte, the mass percentage of the fluorinated sulfonyl imide lithium is H%, and the mass percentage of the fluorinated sulfonic acid additive is S%, satisfying: 1≤H / S≤35.
[0025] In some embodiments, 1≤H / S≤35; H / S is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 35 or a range consisting of any two of the above values. In some embodiments, 5≤H / S≤30. In some embodiments, 8≤H / S≤20. Thus, by controlling the ratio of the content of fluorinated sulfonyl imide lithium and fluorinated sulfonic acid additive, the electrochemical performance and high temperature safety performance of the battery can be effectively improved. When H / S is too large, the corrosion of the current collector aluminum foil cannot be suppressed, resulting in a decline in battery performance; when H / S is too small, the conductivity of the battery electrolyte will decrease and the battery kinetic performance will decrease.
[0026] In some embodiments, based on the mass of the electrolyte, the mass percentage H% of the fluorinated sulfonyl imide lithium satisfies 5≤H≤20, specifically, H% is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range consisting of any two of the above values. In some embodiments, 9≤H≤17. In some embodiments, 12≤H≤15. When the mass percentage of the fluorinated sulfonyl imide lithium is too high, the viscosity of the electrolyte will increase, the conductivity will decrease, and the capacity and kinetic performance of the battery will be affected; when the mass percentage of the fluorinated sulfonyl imide lithium is too low, the corrosion of the current collector aluminum foil will not be effectively suppressed, and the battery performance will deteriorate.
[0027] In some embodiments, based on the mass of the electrolyte, the mass percentage S% of the fluorinated sulfonic acid additive satisfies 0.01≤S≤10, specifically, S% is 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1.5%, 2.5%, 3.5%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the above values. In some embodiments, 0.5≤S≤5. In some embodiments, 2≤S≤5. When the mass percentage of the fluorinated sulfonic acid additive is too high, the conductivity of the electrolyte will decrease and the battery kinetic performance will decrease; when the mass percentage of the fluorinated sulfonic acid additive is too low, the corrosion of the current collector aluminum foil will not be suppressed, resulting in battery performance degradation.
[0028] In the above embodiment, fluorinated sulfonyl imide lithium is used as the lithium salt, and an organic perfluorinated sulfonate fluorinated sulfonic acid additive is used as the anti-corrosion additive, wherein the fluorinated sulfonic acid additive has a lithium sulfonate group, which can be superior to the fluorinated sulfonyl imide lithium to decompose on the surface of the positive electrode current collector aluminum foil, and then react with the aluminum foil to form a dense AlF-rich 3 , and the passivation film of aluminum perfluoroalkyl sulfonate. By controlling the ratio of the content of lithium fluorinated sulfonyl imide and the content of fluorinated sulfonic acid additive, the problem of lithium fluorinated sulfonyl imide corroding the aluminum foil as the positive electrode current collector under high pressure is solved, which significantly improves the cycle performance and rate performance of the secondary battery under high pressure; in addition, the fluorinated sulfonic acid additive can also form a LiF-rich SEI film on the surface of the negative electrode material to improve the kinetic performance of the negative electrode. In addition, the organic part of the fluorinated sulfonic acid additive has large steric hindrance due to factors such as long chain and large volume, and the polarity and surface energy of the fluorinated sulfonic acid additive are reduced after the organic part is fluorinated, thereby ensuring that the fluorinated sulfonic acid additive is not easy to dissolve or swell in the electrolyte, which is beneficial to maintain the stability of the electrolyte. Furthermore, the electrolyte has excellent thermal stability, which greatly improves the high temperature performance and safety performance of the battery.
[0029] In some embodiments, the fluorine-containing lithium sulfonyl imide includes at least one of lithium bisfluorosulfonyl imide, lithium bis(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide, and lithium bis(pentafluoroethylsulfonyl)imide.
[0030] In some embodiments, the fluorine-containing lithium sulfonyl imide includes lithium bis(fluorosulfonyl)imide.
[0031] In some embodiments, the fluorinated sulfonic acid additive comprises at least one of the compounds of Formula 1:
[0032]
[0033] Wherein, L is selected from perfluorocarbon 1 -C 4 Alkylene, R 1 , R 2 and R 3 Each independently selected from fluorine, perfluorinated 1 -C 3 Alkyl, perfluorinated C 1 -C 3 alkenyl, perfluorophenyl or perfluorosilyl.
[0034] It is understood that L is a perfluorinated organic group, and R 1 , R 2 and R 3 All of them include fluorine substituents, which is beneficial to further reduce the polarity and surface energy of the fluorinated sulfonic acid additives, and by 1 , R 2 and R 3 The number and structure of carbon atoms are selected to increase the steric hindrance, thereby making it difficult for the fluorinated sulfonic acid additive to adsorb substances such as solvents in the electrolyte, and thus difficult to dissolve and swell.
[0035] In some embodiments, the fluorinated sulfonic acid additive includes at least one of the following compounds:
[0036]
[0037] In some embodiments, the electrolyte of the present application further includes a first lithium salt, the first lithium salt including lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), at least one of trifluorosulfonyl lithium (LiOTf), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluoromalonate)borate (LiBFMB), lithium 4,5-dicyano-2-(trifluoromethyl)imidazolium (LiTDI) and lithium difluorooxalatoborate (LiDFOB).
[0038] In some embodiments, the concentration of the first lithium salt is 0.01 to 2.0 mol / L. Exemplarily, the concentration of the first lithium salt in the electrolyte is 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L or a range consisting of any two of the above values.
[0039] In some embodiments, the electrolyte further includes an organic solvent, and the organic solvent includes at least one of a linear carbonate, a cyclic carbonate, and a carboxylic acid ester.
[0040] In some embodiments, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, and a fluorinated linear carbonate.
[0041] In some embodiments, the cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, and a fluorinated cyclic carbonate.
[0042] In some embodiments, the carboxylic acid ester includes at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, and a fluorocarboxylic acid ester.
[0043] In some embodiments, the mass percentage of the organic solvent is 10% to 70% based on the mass of the electrolyte. Exemplarily, the mass percentage of the organic solvent is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or a range consisting of any two of the above values based on the mass of the electrolyte.
[0044] In some embodiments, the electrolyte further includes a first additive, the first additive including vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), vinyl sulfate (DTD), 1,3-propene sultone (1,3-PST), vinyl sulfite (ES), tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), methylene disulfonate (MMD S), succinonitrile, adiponitrile, glutaronitrile, hexanetrinitrile, ethyl disulfonate, 1-propylene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), ethylene sulfite (DTO), dimethyl sulfite (DMS) and diethyl sulfite (DES).
[0045] In some embodiments, based on the mass of the electrolyte, the mass percentage of the first additive is 0.01% to 10%; exemplarily, based on the mass of the electrolyte, the mass percentage of the first additive is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or a range consisting of any two of the above values.
[0046] 2. Secondary battery
[0047] One or more embodiments of the present application further provide a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, and the electrolyte of the aforementioned embodiment.
[0048] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector.
[0049] In some embodiments, the positive electrode active material of the positive electrode active material layer includes lithium nickel transition metal oxide. The lithium nickel transition metal oxide includes LiNi x Co y M (1-x-y) O 2 At least one of the following, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1.
[0050] In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide, lithium manganese oxide, and lithium nickel manganese oxide. In some embodiments, the positive electrode active material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92, and Ni95.
[0051] In some embodiments, the positive electrode current collector includes but is not limited to aluminum foil or a composite material containing aluminum. The electrolyte of the present application uses fluorinated sulfonyl imide lithium as a lithium salt, and uses a fluorinated sulfonic acid additive as an anti-corrosion additive, which solves the problem that fluorinated sulfonyl imide lithium corrodes the aluminum foil as the positive electrode current collector under high pressure, and significantly improves the cycle performance and rate performance of the secondary battery under high pressure.
[0052] In some embodiments, the positive electrode active material layer further includes a conductive agent and a binder. The positive electrode active material, the conductive agent, and the binder are fully stirred and mixed in a solvent system (e.g., N-methylpyrrolidone) in a certain proportion, and then coated on an aluminum current collector, dried, and rolled to obtain a positive electrode sheet.
[0053] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0054] In some embodiments, the negative electrode active material of the negative electrode active material layer is at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium.
[0055] In some embodiments, the silicon-based material includes at least one of silicon, silicon alloys, silicon-oxygen compounds, and silicon-carbon compounds.
[0056] In some embodiments, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene.
[0057] In some embodiments, the tin-based material includes at least one of tin, tin oxide, and tin alloy.
[0058] In some embodiments, the phosphorus-based material includes phosphorus and / or a phosphorus-carbon composite.
[0059] In some embodiments, the negative electrode current collector includes, but is not limited to, copper foil.
[0060] In some embodiments, the negative electrode active material layer further includes a conductive agent and a binder. After the negative electrode active material, the conductive agent and the binder are fully stirred and mixed in deionized water in a certain proportion, they are coated on a copper current collector, dried, and rolled to obtain a negative electrode sheet.
[0061] In some embodiments, the leakage current of the secondary battery is TμA / cm2 Satisfies: 0.01≤T≤25. For example, the leakage current of the secondary battery is TμA / cm 2 0.01μA / cm 2 , 0.05μA / cm 2 , 0.1μA / cm 2 , 0.2μA / cm 2 , 0.5μA / cm 2 , 1μA / cm 2 , 2μA / cm 2 , 4μA / cm 2 , 5μA / cm 2 , 6μA / cm 2 , 8μA / cm 2 , 10μA / cm 2 , 12μA / cm 2 , 14μA / cm 2 , 15μA / cm 2 , 16μA / cm 2 , 18μA / cm 2 , 20μA / cm 2 , 21μA / cm 2 , 22μA / cm 2 , 24μA / cm 2 , 24.5μA / cm 2 , 25μA / cm 2 Or a range consisting of any two of the above values. Therefore, when the leakage current is within the above range, the cycle stability of the battery will be improved. When the leakage current is too large, the current collector aluminum foil will be severely corroded, resulting in an increase in the irreversible capacity of the battery, serious gas production of the battery, and a deterioration in the cycle life.
[0062] In some embodiments, the leakage current of the secondary battery is TμA / cm 2 Satisfies: 1≤T≤10. Exemplarily, the leakage current of the secondary battery is TμA / cm 2 1μA / cm 2 , 1.5μA / cm 2 , 2μA / cm 2 , 2.5μA / cm 2 , 3μA / cm 2 、3.5μA / cm 2 , 4μA / cm 2 , 4.5μA / cm 2 , 5μA / cm 2 , 5.5μA / cm 2 , 6μA / cm 2 、6.5μA / cm 2 , 7μA / cm2 , 7.5μA / cm 2 , 8μA / cm 2 、8.5μA / cm 2 , 9μA / cm 2 , 9.5μA / cm 2 , 10μA / cm 2 Or a range consisting of any two of the above values.
[0063] In some embodiments, the secondary battery of the present application may further include a separator, which includes a composite film composed of at least one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid and polyimide films, or a composite film modified by a ceramic material coating.
[0064] 3. Battery Module
[0065] One or more embodiments of the present application further provide a battery module, the battery module comprising the aforementioned secondary battery.
[0066] The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be one or more, and the specific number can be adjusted according to the application and capacity of the battery module.
[0067] 4. Battery Pack
[0068] One or more embodiments of the present application also provide a battery pack, which includes the aforementioned battery module.
[0069] The number of battery modules contained in a battery pack may be one or more, and the specific number may be adjusted according to the application and capacity of the battery pack.
[0070] 5. Device
[0071] One or more embodiments of the present application also provide a device, which includes at least one of the aforementioned secondary battery, battery module and battery pack.
[0072] In some embodiments, the device of the present application includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.
[0073] In some embodiments, the devices of the present application include but are not limited to: laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.
[0074] The technical solution of the present application will be further illustrated below with reference to specific embodiments and comparative examples.
[0075] Examples and Comparative Examples
[0076] Example 1
[0077] The steps of preparing the positive electrode, the negative electrode, the electrolyte, the separator and the battery are described as follows. 0.9 Co 0.05 Mn 0.05 O 2 ; The negative electrode active material is artificial graphite, and the coating surface density is determined according to the battery size, capacity design and the capacity of the positive and negative electrode materials.
[0078] The positive electrode preparation steps are: 0.9 Co 0.05 Mn 0.05 O 2 , conductive agent carbon nanotube / acetylene black, binder polyvinylidene fluoride PVDF, by weight ratio LiNi 0.9 Co 0.05 Mn 0.05 O 2 : CNT / Super-P: PVDF=95:2.0 / 1.0:2 was fully slurried in N-methylpyrrolidone NMP solvent system, coated on a 12 μm thick aluminum-coated current collector, dried, and roll-pressed to obtain a positive electrode sheet.
[0079] The negative electrode preparation steps are as follows: artificial graphite, a negative electrode active material, acetylene black, a binder styrene-butadiene rubber SBR, a thickener sodium carboxymethyl cellulose CMCNa, and polyacrylic acid PAA are fully slurried in a deionized water solvent in a weight ratio of 95:2:1.5:1:0.5, and then coated on the surface of a 8 μm thick copper current collector, and then dried, rolled, and slit to obtain a negative electrode sheet.
[0080] The diaphragm is a PP / PE / PP three-layer composite diaphragm.
[0081] Preparation of electrolyte: In a glove box filled with argon (H 2 O<0.1ppm,O 2 <0.1ppm), ethylene carbonate, propylene carbonate, diethyl carbonate and ethyl methyl carbonate are mixed in a mass ratio of EC:DEC:EMC=25:20:55, and then 17wt% of lithium bis(fluorosulfonyl)imide (LiFSI) based on the total weight of the electrolyte is slowly added to the mixed solution, and finally 1wt% of the compound of formula 2 based on the total weight of the electrolyte is added as a fluorinated sulfonic acid additive, and the lithium ion battery electrolyte of Example 1 is obtained after stirring evenly.
[0082] Preparation of lithium-ion battery: stack the prepared positive electrode sheet, separator and negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets, and wind them to obtain a bare battery cell; place the bare battery cell in an aluminum-plastic film outer packaging, and inject the prepared lithium-ion power battery electrolyte into the fully dried artificial graphite / LiNi 0.9 Co 0.05 Mn 0.05 O 2 In the battery, the battery was placed at 45°C, formed in a high-temperature fixture (the formation conditions were: temperature 45°C, pressure 210kgf, 0.05C current charging to 4.25V and standing for 60min, then 0.1C charging to 4.25V, and then 0.2C discharge to 3.0V, and this was repeated three times) and secondary sealing before conventional capacity division.
[0083] Examples 2 to 17 and Comparative Examples 1 to 9
[0084] The only difference between Examples 2 to 17 and Comparative Examples 1 to 9 and Example 1 is that at least one of the type and mass percentage of the fluorinated sulfonic acid lithium imide, the type and mass percentage of the first lithium salt, the type and mass percentage of the fluorinated sulfonic acid additive, and the type and mass percentage of the first additive in the electrolyte is changed.
[0085] The rest of the preparation methods of Examples 2 to 17 and Comparative Examples 1 to 9 are the same as those of Example 1. Specific adjustment measures and detailed data are shown in Table 1.
[0086] Table 1
[0087]
[0088]
[0089] Test Method
[0090] 1. Leakage current test:
[0091] The battery after capacity conversion was float-charged at a constant voltage of 4.5 V using an electrochemical workstation to obtain a stable current-time It curve. The current value after 12 hours was read, which was the leakage current of the battery.
[0092] 2. Cycle capacity retention rate test:
[0093] At 25°C, the lithium-ion battery was charged to 4.25V at 1C constant current and constant voltage, and then discharged to 2.5V at 1C constant current. After 500 cycles of charge and discharge, the capacity retention rate after the 500th cycle at 25°C was calculated according to the following formula: discharge capacity after the 500th cycle / discharge capacity in the first cycle×100%.
[0094] At 45°C, the lithium-ion battery was charged to 4.25V at 1C constant current and constant voltage, and then discharged to 2.5V at 1C constant current. After 500 cycles of charge and discharge, the capacity retention rate after the 500th cycle at 45°C was calculated according to the following formula: discharge capacity after the 500th cycle / discharge capacity in the first cycle × 100%.
[0095] 3. Expansion rate test:
[0096] The battery was discharged to 3.0V at 0.5C at 25°C, charged to 4.45V at 0.5C, and charged to 0.05C at 4.45V. The thickness of the battery at this time was measured using a PPG soft pack battery thickness gauge and recorded as a. The battery was placed in an oven and stored at a constant voltage of 4.45V at 45°C for 21 days. The thickness of the battery after 21 days was recorded as b. The thickness expansion rate was calculated as: (ba) / a×100%.
[0097] Table 2
[0098]
[0099]
[0100] Table 2 shows the test results of the cycle capacity retention rate, expansion rate, leakage current and corrosion of the positive electrode current collector aluminum foil of the secondary batteries in Examples 1 to 17 and Comparative Examples 1 to 10.
[0101] It can be seen from Examples 1 to 7 and Comparative Example 1 that after adding the fluorinated sulfonic acid additive to the electrolyte, the electrolyte has no obvious corrosion to the aluminum foil, the leakage current is significantly reduced, and the cycle capacity retention rate and expansion problems of the lithium battery are significantly improved. Further, in combination with Comparative Example 2, it can be seen that the content of the fluorinated sulfonic acid additive is too high, and the H / S value does not meet the preset relationship, which will cause the electrolyte conductivity to decrease and affect the battery's kinetic performance and capacity. This is because the fluorinated sulfonic acid additive contains a long-chain perfluorocarbon segment with low polarity, which will reduce the dissociation degree of the solvent multi-lithium salt, thereby reducing the conductivity of the electrolyte. Further, in combination with Comparative Example 3, the content of the fluorinated sulfonic acid additive is too low, and the H / S value does not meet the preset relationship, which will cause the positive electrode current collector aluminum foil to corrode. This is because when the content of the fluorinated sulfonic acid additive is too low, the passivation film formed on the surface of the current collector is not enough to resist the corrosion of the electrolyte with a higher LiFSI content.
[0102] It can be seen from Examples 9 to 13 that adding different perfluoroalkyl sulfonic acid lithium salt compound additives has a good improvement effect on the high-temperature cycle stability of the battery, and has a good passivation effect on aluminum foil. It can be seen from Examples 7, 8, and 13 that on the basis of the electrolyte containing fluorinated sulfonic acid additives, further adding the first additive (such as VC and FEC, VC and PS, etc.) can further improve the high and low temperature cycle performance of the lithium battery. It can be seen from Examples 4 and Examples 14 to 17 that when the total mass percentage of lithium salt in the electrolyte remains unchanged, the use of LiPF 6 When LiFSI is partially replaced by LiFSI, as long as the content H% of LiFSI satisfies 5≤H≤20, a relatively high cycle capacity retention rate can still be maintained.
[0103] In addition, it can be seen from the comparison of Example 1 and Examples 4 to 10 that when the first additive is added to the electrolyte without adding the fluorinated sulfonic acid additive, not only the positive electrode current collector aluminum foil of the lithium battery will be severely corroded, but also the leakage current will increase significantly, thereby significantly reducing the cycle capacity retention rate of the lithium battery. Furthermore, it can be seen from the comparison of Examples 5 to 9 that even if LiPF 6 To partially replace LiFSI, without using fluorinated sulfonic acid additives, the positive electrode current collector aluminum foil is still not able to avoid being corroded by the electrolyte, and the leakage current is large, and the improvement of the cycle capacity retention rate and the expansion rate is not obvious. In addition, referring to Comparative Examples 8 to 10, it can be seen that without adding fluorinated sulfonic acid additives to the electrolyte, other additives (for example, LiBOB, LiDFOB) are used in combination with the first additive. Although it can alleviate the corrosion problem of the positive electrode current collector aluminum foil, the effect is limited, and the leakage current, the cycle capacity retention rate and the expansion rate of the lithium battery are not significantly improved. It can be seen that the fluorinated sulfonic acid additive and the first additive can play a synergistic role, thereby achieving the improvement of the comprehensive performance of the lithium battery.
[0104] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. An electrolyte, characterized in that: include: Fluorinated lithium sulfonyl imide and a fluorinated sulfonic acid additive, wherein the fluorinated sulfonic acid additive comprises RL-SO3M; wherein L is selected from fluorinated C1-C6 alkylene or fluorinated C1-C6 alkenylene, and R is selected from fluorine, fluorinated C1-C6 alkyl, fluorinated C1-C6 alkenyl, fluorinated C6-C 12 Aryl or fluorosilyl, M is selected from lithium or sodium; Based on the mass of the electrolyte, the mass percentage of the fluorinated sulfonyl imide lithium is H%, the mass percentage of the fluorinated sulfonic acid additive is S%, and the following conditions are satisfied: 1≤H / S≤35.
2. The electrolyte according to claim 1, characterized in that The fluorine-containing lithium sulfonyl imide comprises at least one of lithium bisfluorosulfonyl imide, lithium bis(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide and lithium bis(pentafluoroethylsulfonyl)imide; and / or The fluorinated sulfonic acid additive includes at least one of the compounds shown in Formula 1: Wherein, L is selected from perfluoro C1-C4 alkylene, and R1, R2 and R3 are each independently selected from fluorine, perfluoro C1-C3 alkyl, perfluoro C1-C3 alkenyl, perfluoro phenyl or perfluoro silyl.
3. The electrolyte according to claim 1 or 2, characterized in that The fluorine-containing lithium sulfonyl imide comprises lithium bis(fluorosulfonyl)imide; and / or The fluorinated sulfonic acid additive comprises at least one of the following compounds:
4. The electrolyte according to claim 1, characterized in that 5≤H / S≤30; and / or, 5≤H≤20; and / or, 0.01≤S≤10.
5. The electrolyte according to claim 4, characterized in that 8≤H / S≤20; and / or, 9≤H≤17; and / or, 0.5≤S≤5.
6. The electrolyte according to claim 1, characterized in that The electrolyte also satisfies at least one of the following conditions: (1) The electrolyte further includes a first lithium salt, wherein the first lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluorosulfonyl, lithium bis(oxalatoborate), lithium bis(fluoromalonate)borate, lithium 4,5-dicyano-2-(trifluoromethyl)imidazole and lithium difluorooxalatoborate; and the concentration of the first lithium salt is 0.01 mol / L to 2.0 mol / L; (2) The electrolyte further includes an organic solvent, and the organic solvent includes at least one of a chain carbonate, a cyclic carbonate, and a carboxylic acid ester; wherein the chain carbonate includes at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, and a fluorinated chain carbonate; the cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, and a fluorinated cyclic carbonate; the carboxylic acid ester includes at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, and a fluorinated carboxylic acid ester; and the mass percentage of the organic solvent is 10% to 70% based on the mass of the electrolyte; (3) The electrolyte also includes a first additive, the first additive including at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, vinyl sulfate, 1,3-propene sultone, vinyl sulfite, tris(trimethylsilyl) phosphate, tris(trimethylsilyl) borate, methylene disulfonate, succinonitrile, adiponitrile, glutaronitrile, hexanetrinitrile, ethyl disulfonate, 1-propylene-1,3-sultone, 1,4-butane sultone, 4-methyl ethylene sulfate, 4-ethyl ethylene sulfate, 4-propyl ethylene sulfate, propylene sulfate, ethylene sulfite, dimethyl sulfite and diethyl sulfite; based on the mass of the electrolyte, the mass percentage of the first additive is 0.01% to 10%.
7. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and the electrolyte according to any one of claims 1 to 6.
8. The secondary battery according to claim 7, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector; the positive electrode active material of the positive electrode active material layer comprises lithium nickel transition metal oxide; the lithium nickel transition metal oxide comprises LiNi x Co y M (1-x-y) O2, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1; the material of the positive electrode current collector includes aluminum; and / or The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector, the negative electrode active material of the negative electrode active material layer comprises at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium; the silicon-based material comprises at least one of silicon, a silicon alloy, a silicon oxide compound and a silicon-carbon compound, the carbon-based material comprises at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene, the tin-based material comprises at least one of tin, tin oxide and a tin alloy, and the phosphorus-based material comprises phosphorus and / or a phosphorus-carbon composite; and / or The leakage current of the secondary battery is TμA / cm 2 Satisfies: 0.01≤T≤25.
9. The secondary battery according to claim 8, characterized in that: The leakage current of the secondary battery is TμA / cm 2 Satisfies: 1≤T≤10.
10. A device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 7 to 9.
Citation Information
Cited By
Lithium ion battery and electric device
CN120319872A
Battery cell, battery device and electric device
CN120581697A